Developments in the global hydrogen market: The spectrum of hydrogen colours. Issue 11 (November 2020) - Newborough, Marcus; Cooley, Graham
Abstract : The fundamental reasons for considering the adoption of hydrogen as a fuel, industrial feedstock and energy storage medium are presented. Hydrogen production methods are outlined, with reference to the colour prefixes used to describe different types of hydrogen. The relative greenhouse gas emissions and economics of green and blue hydrogen production are considered for achieving a 'net zero' climate-neutral energy system by 2050. In general, it appears that green hydrogen will soon be cheaper than blue hydrogen due to the falling costs of renewable electricity and electrolysers, then cheaper than grey hydrogen, and in the long term potentially cheaper than natural gas.